1524. Are Providers Shifting from NTF to Fosfomycin for Inpatient UTI? Big Data Reveals Small Shifts. (26th November 2018) - Gupta, Kalpana; Goetz, Matthew B; Jones, Makoto; Strymish, Judith M
Abstract: Background: Fosfomycin (FOS) and NTF (NTF) are IDSA guideline approved drugs for acute cystitis in women. However, their activity against multi drug-resistant Gram-negatives may be driving increased use among inpatients with more complicated UTI. We evaluated trends in inpatient prescribing of these UTI-specific agents in the predominantly male population of the national VA system over a 7-year period. Methods: All inpatient bar coded administrations for FOS and NTF at every VA facility nationwide from 2011 to 2017 were captured through a data analytics platform which extracts data from the VA Data warehouse. Antibiotic days of therapy and rates per 1, 000 patient-days (DOT/1, 000CD) were extracted by year and compared using Mantel-Haenszel chi square for linear trend (MH OR). Demographics were captured via administrative data. Results: Prescriptions from over 65 million patient-days spanning 7 years and all inpatient units in 129 VA facilities were included. Approximately 90% of patients were male with a mean age range of 55–64 years. FOS use increased from 128 prescriptions in 2011 to a high of 1, 230 in 2016 and 1, 003 in 2017 (figure). At the maximum in 2016, prescription rates increased almost 10-fold compared with 2011 (MH OR 9.8, P < 0.001). NTF prescriptions declined from 26, 590 in 2011 to 19, 343 in 2017. Rates decreased 25% from 2.8 to 2.1, MH OR 0.75, P < 0.001. In 2017, FOS and NTF usage rates were highest in rehabilitation/spinal cord units (table). Conclusion: In this large nationwide cohort, FOS use increased almost 10-fold among predominantly male inpatients while NTF use declined slightly. NTF is still used orders of magnitude more than FOS, even after adjusting for extended days of activity of FOS. Both agents retain activity against many MDR GNRs but differences in efficacy, tissue penetration, familiarity and availability likely influence the choice for oral UTI-specific treatment. Disclosures: All authors: No reported disclosures.